Accounting for cross boundary flows. Issue 6603 (10th October 1987) - Brazier, J
Abstract : RAWP (Resource Allocation Working Party) allows for cross boundary flows by adjusting regional or district health authorities' (DHAs) targets at an average specialty cost. The previous paper in this series examined problems for an inner city district health authority arising from RAWP cross boundary flow adjustment. This paper examines the likely importance of these and other problems for the National Health Service as a whole. Cross charging has been proposed as an alternative method of funding flows. District health authorities would receive an allocation equivalent to their RAWP target and then all non-emergency flows would be agreed between the authorities where patients live and competing authorities offering treatment at previously negotiated charges based on local estimates of each type of case. The problem of cost estimation is usually cited as a difficulty with this proposed reform, but this paper also discusses other important issues that tend to be neglected.